2020
DOI: 10.3390/molecules25102342
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Compounds Inhibit High Glucose-Induced Inflammation by Regulating NF-κB Signaling in Human Monocytes

Abstract: High glucose-induced inflammation leads to atherosclerosis, which is considered a major cause of death in type 1 and type 2 diabetic patients. Nuclear factor-kappa B (NF-κB) plays a central role in high glucose-induced inflammation and is activated through toll-like receptors (TLRs) as well as canonical and protein kinase C-dependent (PKC) pathways. Non-toxic sulfur (NTS) and methylsulfonylmethane (MSM) are two sulfur-containing natural compounds that can induce anti-inflammation. Using Western blotting, real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…NTS is a form of non-toxic mineral sulfur. Studies have shown the ability of NTS to enhance growth hormone signaling via the JAK2/STAT5b/IGF-1 axis and to produce anti-inflammatory effects against hyperglycemia in human monocytes [22,35]. MSM is another sulfur-containing natural compound with…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…NTS is a form of non-toxic mineral sulfur. Studies have shown the ability of NTS to enhance growth hormone signaling via the JAK2/STAT5b/IGF-1 axis and to produce anti-inflammatory effects against hyperglycemia in human monocytes [22,35]. MSM is another sulfur-containing natural compound with…”
Section: Discussionmentioning
confidence: 99%
“…NTS is a form of non-toxic mineral sulfur. Studies have shown the ability of NTS to enhance growth hormone signaling via the JAK2/STAT5b/IGF-1 axis and to produce anti-inflammatory effects against hyperglycemia in human monocytes [ 22 , 35 ]. MSM is another sulfur-containing natural compound with various anti-inflammatory activities [ 38 ] and exercise-induced stress in racing horse muscle cells via p53-mediated SDHA/HPRT1 expression [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations